THE DEVELOPMENT OF FUNDAMENTAL SCIENCE: STRATEGIES AND MECHANISMS FOR SETTING PRIORITIES - S. I. Ostapyuk (Modernizaciâ, Innovaciâ, Razvitie, 2018)
Purpose: the aim of paper is comparison of various strategies for the development of fundamental science and the formation of procedures for selecting priorities for the development of fundamental scientific research for the strategies examined.Methods: the research is basedonasystematicapproachtoimprovingthestrategicmanagementofthedevelopmentofbasicscientificresearch. Methodical basis of the research are methods of systematization, synthesis, generalization, analogies, classification, situational analysis, analysis of empirical and expert data.Results: an analysis of four possible strategies for the development of fundamental scientific research in the Russian Federation was carried out. Their positive and negative sides are revealed, risks of their realization are highlighted. For each strategy, a procedure is proposed for selecting priorities for the development of basic scientific research. The possible impact of strategies on national security and economic development in the long term is shown. Comparison of these strategies is carried out.conclusions and relevance: according to the authors, the most favorable from the point of view of scientific, technological and socio-economic development of the country is the Strategy for the Development of Basic Research on a Broad Front. However, it requires an increase in the resource provision of science and a change in approaches to the management of science. Next on attractiveness is the compilation of two strategies – the Development Strategy for a narrow specialization and the Strategy of catching-up development for the rest of research. Depending on the chosen strategy for the development of fundamental science, it is necessary to give a different list of works on the formation of priorities for fundamental research, the description of which is given for each strategy considered.